Prevalence of attention deficit hyperactive disorder (ADHD) symptoms in selected government primary schools in Wakiso District, Uganda - Josephine Ssirimuzaawo; Miph Musoke; Pio Frank Kiyingi (Quality Education for All)
Purpose – This paper on the prevalence of attention deficit hyperactive disorder (ADHD) in schools holds immense significance due to its unique contribution to the existing body of knowledge. This study stands out as one of the few conducted in Uganda and the entire African continent. The purpose of this study is to establish the prevalence of ADHD symptoms in government primary schools in Wakiso District, Uganda. And also inform educational policies and interventions tailored to address the needs of children with ADHD in Uganda and globally. Design/methodology/approach – The research paradigm adopted was pragmatism, an explanatory sequential mixed methods approach was used, with a quantitative sample of 1,067 participants (learners), 64 teachers who underwent a series of training to equip them with the necessary knowledge about ADHD filled questionnaires for the 1,067 learners, four teachers selected in each school, one teacher per class and a qualitative sample of 32 teachers and one key informant from 16 primary schools. Random and purposive sampling was used. The strengths and weaknesses of ADHD symptoms and normal behavior scale questionnaire was used for quantitative data collection, while qualitative data was gathered through interviews, observations and focus group discussion. Findings – The results revealed an overall prevalence of ADHD symptoms of 11.60%, with inattention symptoms being more dominant than hyperactive/impulsivity symptoms (8.82%). There was no significant difference in prevalence between boys and girls, with primary one pupils having the highest prevalence of symptoms and primary four pupils having the lowest. Pupils aged 10–13 may be less susceptible to ADHD symptoms. The most prevalent symptoms were linked to interrupting or intruding behavior, failure to give attention to detail and inability to play quietly. Qualitative data from the key informant’s observations and teacher focus groups supported these findings. Research limitations/implications – Limited geographic scope: The study was conducted in only one district, Wakiso, in Uganda. However, this district is very densely populated with people from different cultural and economic background, making it representative of the entire country Uganda. While the response rates for both the quantitative and qualitative components were relatively high (95% and 84%, respectively), there is a possibility that those who chose to participate may have different experiences. But the response rate provided sufficient data for analysis according to the researcher. Practical implications – The researcher recommends that further research is needed in other districts; also, there is a need to develop early intervention strategies for teachers and parents with ADHD children. More research is needed to better understand the primary causes and risk factors associated with ADHD in primary school children. Originality/value – This study stands out as one of the few conducted in Uganda and the entire African continent on ADHD. By addressing this research gap, the paper adds valuable insights to the field of ADHD research, shedding light on the prevalence of ADHD symptoms, which can be used to investigate the impact of ADHD on academic performance within the Ugandan education system further. The findings of this study have the potential to inform educational policies and interventions tailored to address the needs of children with ADHD in Africa and beyond.